ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM PENGENDALIAN PERSEDIAAN BARANG (Studi Kasus Pada Toko Ponsel Twentyone Kota Sukabumi) - Putri, Adinda Yasmine (Jurnal Ilmu Akuntansi, 2023)
This study aims to determine and explain the analysis of the application of accounting information systems in inventory control at the Twentyone Cellphone Shop, Sukabumi City. This research was conducted at the Twentyone Cellphone Shop, Sukabumi City, with the respondents being the Employees of the Twentyone Cellphone Shop, Sukabumi City. Data collection was carried out by observing, interviewing and studying the literature. The results of the data collection are processed and described in narrative form. The results of this study indicate that the Twentyone Cellphone Shop in Sukabumi City has not implemented an adequate inventory accounting information system and cannot properly separate each function, because there are still multiple tasks between employees which can pose a risk of confusion. In addition, the organizational structure of the Twentyone Sukabumi Cell Phone Shop is still very simple so that in the inventory section there are still multiple tasks, resulting in a lack of supervision over inventory control.